Organic-inorganic multi-layer composite coating material with functions of promoting cell adhesion, resisting infection and promoting osteogenesis and preparation method of organic-inorganic multi-layer composite coating material

By constructing a multi-layer composite coating on the surface of a titanium/titanium alloy substrate, the problems of postoperative infection and low osteogenic efficiency in orthopedic and dental implants have been solved, achieving highly efficient antibacterial and osteogenic effects and improving cell adhesion efficiency.

CN121668384APending Publication Date: 2026-03-17ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511955964.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-23
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing orthopedic and dental implants face problems such as high postoperative infection rates, low osteogenic efficiency, and insufficient cell adhesion. Furthermore, existing coating materials are difficult to combine in a synergistic manner in terms of antibacterial and osteogenic functions.

Method used

Using multi-layer composite coating materials, copper/zinc alloy underlayer and PDA-Fe3+-tanshinone b layer are constructed on the surface of titanium/titanium alloy substrate through glow discharge cleaning, electrochemical deposition, sandblasting, in-situ self-polymerization and ultrasonic impregnation technology, forming topological morphology and antibacterial structure, promoting cell adhesion and osteogenic formation.

Benefits of technology

It achieves a high antibacterial rate, significantly shortens the bone integration cycle, and improves cell adhesion efficiency and bone repair speed, providing highly effective anti-infection and bone function promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121668384A_ABST
    Figure CN121668384A_ABST
Patent Text Reader

Abstract

The invention discloses an organic-inorganic multi-layer composite coating material with functions of promoting cell adhesion, resisting infection and promoting osteogenesis and a preparation method of the organic-inorganic multi-layer composite coating material. The method specifically comprises the following steps: 1) carrying out primary sand blasting treatment on a titanium / titanium alloy sample, then removing an oxide layer on the surface of the titanium / titanium alloy sample by using an ultrasonic oil removal and glow discharge cleaning process, and constructing a copper / zinc alloy coating on the surface of the sample by combining an electrochemical deposition process; 2) carrying out micro-nano processing on the coating by using a secondary sand blasting process to introduce a topological morphology; (3) depositing a polydopamine PDA coating on the surface by using an in-situ auto-polymerization process, and simultaneously dipping to complete the chelation of Fe < 3 + > and PDA; 4) further utilizing an ultrasonic impregnation process to realize conversion from PDA-Fe < 3 + > chelation to PDA-Fe < 3 + >-salvianolic acid b chelation so as to introduce a salvianolic acid b layer, and washing, air-drying and sterilizing to obtain the material. The material has multiple cell adhesion promotion, infection resistance and multiple osteogenesis promotion functions, and can realize innovation of coating technologies in the fields of orthopedics, dentistry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional composite coating materials technology, specifically relating to an organic-multilayer composite coating material that combines cell adhesion promotion, anti-infection, and osteoproliferative functions, and its preparation method. Background Technology

[0002] With the increasing global population aging, the demand for medical care in fields such as orthopedics and dentistry continues to grow. The current market size for bone implant devices has climbed to $47.1 billion, maintaining a compound annual growth rate of 3.7%. However, the industry faces two major challenges: the average postoperative infection rate in orthopedic surgeries has long been above 10%, and the integration period between implants and bone tissue is generally as long as 3-6 months, imposing a significant physiological, psychological, and economic burden on patients.

[0003] With the development of coating technology, coatings such as hydroxyapatite, copper, zinc, and silver have shown great promise in bone repair and antibacterial applications, bringing hope to patients. However, most current coating materials only possess single antibacterial or osteogenic functions, and there are still technical challenges in achieving a synergistic combination of long-lasting antibacterial and efficient bone repair functions. Furthermore, many antibacterial coatings even have the opposite effect on osseointegration, becoming a key bottleneck restricting industrial upgrading. Therefore, the development of a multifunctional composite coating material that combines anti-infection, promotes osseointegration, and efficiently promotes bone formation would represent a significant technological innovation for the fields of orthopedics and dentistry.

[0004] Based on this, this invention develops an organic-inorganic multilayer composite coating material with triple functions of promoting cell adhesion, anti-infection, and promoting osteolysis. This technology innovatively integrates advanced techniques such as glow discharge cleaning, electrochemical deposition, sandblasting surface treatment, in-situ self-polymerization reaction, and ultrasonic impregnation to successfully construct a composite coating system with a precise hierarchical structure on the surface of titanium and titanium alloy substrates. The coating design employs a synergistic optimization strategy of micro-nano scale structure and chemical composition, achieving not only an antibacterial rate of over 99% and a significantly shortened osteointegration period, but also significantly improving cell adhesion efficiency through biomimetic interface engineering. As a significant breakthrough in bone implant coating technology, this achievement will strongly promote the development of orthopedic and dental implants towards functional integration and clinical efficiency, possessing significant industrial upgrading value and broad market application prospects. Summary of the Invention

[0005] This invention aims to address common problems faced by implanted devices in the fields of orthopedics and dentistry, such as postoperative infection, low osteogenic efficiency, and insufficient cell adhesion. By developing organic-inorganic multilayer composite coating materials and their preparation methods that combine cell adhesion promotion, anti-infection, and osteogenic functions, this invention provides innovative solutions for related fields.

[0006] This invention is achieved using the following technical solution: 1) The titanium / titanium alloy sample was first sandblasted, and then ultrasonic degreasing and glow discharge cleaning processes were used in sequence to remove the oxide layer on the surface of the titanium / titanium alloy sample. Then, a copper / zinc alloy coating with antibacterial and osteogenic functions was quickly constructed on the sample surface by electrochemical deposition process. 2) The above coating is micro- or nano-processed using a second sandblasting process to introduce a topological morphology that facilitates cell adhesion; 3) A polydopamine (PDA) coating was deposited on the sample surface using an in-situ self-polymerization process, followed by impregnation to complete the Fe... 3+ Chelation with PDA; 4) Further utilize ultrasonic impregnation technology to achieve PDA-Fe 3+ Chelation to PDA-Fe 3+ The tanshinone b chelate conversion introduces a tanshinone b layer that promotes cell adhesion, and the coating is obtained after rinsing, air drying and sterilization.

[0007] Furthermore, the first sandblasting process in step 1) is as follows: an intake-type pneumatic sandblasting system is used, equipped with a 200-350W drive motor and a 6-9kW air compressor. Under a compressed air pressure of 0.4-0.7MPa, 80-120 mesh and 200-220 mesh white corundum abrasive particles are accelerated to 50-100m / s and sprayed onto the sample surface. During the operation, the spray gun is aimed at the workpiece at a 30-60° angle and a dynamic spray angle distance of 100-300mm is maintained. The sandblasting time is 5-30s, and a micro-nano composite structure with a surface roughness (Ra) value of 1-5 micrometers is controllably constructed on the surface. The ultrasonic degreasing process is as follows: The sample is placed in an ultrasonic cleaning solution and immersed for 20-30 minutes at an ultrasonic degreasing power of 100-180W and a solution temperature of 50-60℃. Then, it is rinsed three times with deionized water, each time for 10-15 minutes. The ultrasonic cleaning solution formula is: sodium hydroxide 20-30 g / L, sodium carbonate 8-16 g / L, sodium metasilicate pentahydrate 10-15 g / L, fatty alcohol polyoxyethylene ether 3-5 g / L, sodium citrate 2-5 g / L, sodium polyacrylate 1-4 g / L, benzotriazole 0.5-1 g / L, with the remainder being deionized water. The glow discharge cleaning process is as follows: The sample is placed in a vacuum chamber and evacuated to 5*10... -3After Pa, a mixture of argon and oxygen is injected, with an argon flow rate of 50-100 sccm and an oxygen flow rate of 30-200 sccm. The vacuum is then evacuated again to 1-3 Pa. The workpiece is heated to a temperature of 150-200℃, and a negative bias voltage of 600-1000V is applied with a duty cycle of 50-80%. The bombardment cleaning time is 900-1500s. The electrochemical deposition process is as follows: The sample is placed in an electrolyte solution with a pH of 9.5-11, heated and kept at a constant temperature of 45-50℃. The copper / zinc alloy electrolyte formula is: copper pyrophosphate 25-35 g / L, zinc sulfate 15-50 g / L, potassium pyrophosphate 200-280 g / L, sodium citrate 10-18 g / L, potassium sulfate 12-25 g / L, sodium hydroxide 2-6 g / L, polyethylene glycol 4000 0.6-1.5 g / L, potassium antimony tartrate 0.5-0.9 g / L, and the remainder is deionized water. Copper is used as the anode, and the sample is used as the cathode, with an A / dm³ flow rate of 0.3-0.5. 2 A dual-pulse power supply (duty cycle 50%) was used to continuously filter the electrolyte under mechanical stirring at 50-300 rpm / min, and the deposition time was 30-130 min to obtain a copper-zinc composite coating. The final copper-zinc mass ratio of the coating was controlled at 75:25-30:70.

[0008] Furthermore, the second sandblasting process in step 2) is as follows: an intake-type pneumatic sandblasting system is used, equipped with a 200-350W drive motor and a 6-9kW air compressor. 20-300 mesh green silicon carbide abrasive is used with compressed air pressure of 0.5-0.8MPa, accelerated to 50-100m / s and sprayed onto the coating surface. During operation, the spray gun is aimed at the workpiece at a 30-60° angle, maintaining a dynamic spray angle distance of 100-300mm. The sandblasting time is 5-30s, and a topological morphology containing pits with a diameter of 1-100 micrometers can be controllably constructed on the surface.

[0009] Furthermore, the in-situ self-polymerization process in step 3) specifically involves: placing the sample in a dopamine PDA coating solution and polymerizing it at 30-35°C for 4-15 hours; subsequently, immersing the polymerized sample in Fe... 3+ The dopamine PDA coating solution is prepared by immersion chelation in an aqueous solution. The formulation includes: dopamine hydrochloride 2-8 g / L, chitosan 2-5 g / L, polyvinylpyrrolidone 2-4 g / L, nano-hydroxyapatite 20-100 mg / L, and a Tris-HCl buffer solution with a pH of 8.5-9. The Fe... 3+ The aqueous solution concentration is 0.02-0.10 mol / L, Fe 3+The sample is derived from one or more of ferric chloride, ferric nitrate, and ferric sulfate, with a solution temperature of 25-35℃ and an immersion time of 40-70 minutes. Further, the ultrasonic immersion process in step 4) specifically involves immersing the sample in a tanshinone b chelate solution. The tanshinone b chelate solution has the following formulation: tanshinone b 2-3 g / L, ethanol 80-120 mL / L, ascorbic acid 0.5-1.2 g / L, sodium chloride 6-10 g / L, sodium hyaluronate 0.05-1 g / L, chitosan quaternary ammonium salt 0.1-3 g / L, using 10 mM Tris-HCl buffer (pH 7.4) as the solvent system. The temperature of the tanshinone b chelate solution was controlled at 25-35℃, and the ultrasonic power was 20-70W for immersion for 15-30 minutes. After the step, it was rinsed with deionized water 3-5 times, and the surface moisture was dried with high-purity nitrogen at a flow rate of 10-20 m / s. The above operation was repeated 3-6 times, and the surface was dried with forced air at 40-50℃ for 50 minutes. Finally, it was vacuum sealed in an aluminum foil bag to protect it from light. 60 The material is obtained by irradiation sterilization at a Co dose of 15-25 kGy.

[0010] Compared with the prior art, the present invention has the following advantages: 1) This invention uses titanium / titanium alloy as a base and innovatively employs copper / zinc alloy, polydopamine, tanshinone b, and Fe-containing... 3+ Using raw materials such as compounds and through an original combination of processes, including glow discharge cleaning, electrochemical deposition, double sandblasting micro-nano processing, in-situ self-polymerization, and ultrasonic impregnation technology, a multi-layer composite coating material with multiple biological functions, including promoting cell adhesion, anti-infection, and promoting osteolysis, has been successfully prepared.

[0011] 2) The multilayer composite coating material in this invention has a unique multilayer structure design: a copper-zinc alloy base layer with topological morphology + PDA-Fe 3+ - Tanshinone B layer can synergistically meet the functional requirements of promoting cell adhesion, anti-infection, and osteogenic processes. Among them, PDA-Fe formed on the outermost layer of the sample through in-situ self-polymerization and ultrasonic impregnation process. 3+ - Tanshinone B layer, which has significant biological activity, can promote cell adhesion and proliferation on the coating surface, providing a good cellular and drug basis for subsequent bone integration and bone repair; and it is precisely the PDA-Fe in it that... 3+ The layer connects the underlying alloy layer and the tanshinone b active component in the surface layer, achieving structural organic integration of inorganic and organic components. The underlying copper / zinc alloy layer with its topological morphology is an active, osteogenic, and antibacterial layer fabricated using an electrochemical deposition process. On one hand, the topological morphology introduced into the alloy layer during the sandblasting process allows the tanshinone b-induced adhesion and proliferation of cells to better adhere and attach to the coating surface. On the other hand, the alloy coating can release Cu with antibacterial properties.2+ It effectively inhibits bacterial growth and reproduction, prevents biofilm formation, and reduces the risk of postoperative infection. The Zn released from the alloy coating... 2+ It can promote further osteogenic differentiation of adherent cells, thereby accelerating the efficient repair of bone defects. The multi-layered structure design allows each functional layer to work synergistically from the inside out, effectively resisting infection while promoting cell adhesion and osteogenic function, which is the core structural innovation of this invention.

[0012] 3) This invention innovatively integrates processes such as primary sandblasting, ultrasonic degreasing, glow discharge cleaning, electrochemical deposition, secondary sandblasting micro-nano processing, in-situ self-polymerization, and ultrasonic impregnation to efficiently construct a multi-layer composite coating. Primary sandblasting introduces a rough physical structure onto the substrate surface, and the combined glow discharge cleaning process deeply cleans the titanium / titanium alloy substrate surface, significantly enhancing the adhesion between the coating and the substrate, laying the foundation for subsequent coating preparation. During electrochemical deposition, precise control of the copper / zinc alloy deposition parameters (such as electrolyte formulation and deposition voltage) results in a uniform coating with excellent antibacterial properties. Sandblasting micro-nano processing creates micro-nano structures on the substrate surface, providing more adhesion sites for cells. In-situ self-polymerization and ultrasonic impregnation ensure the organic integration of organic components such as polydopamine and tanshinone b on the inorganic metal coating surface, thereby enabling them to exert their functions of promoting cell adhesion and osteogenic processes. This invention, for the first time, addresses the complex clinical problem of infectious bone defects by organically combining the above-mentioned processes to meet actual clinical needs. This results in the precise preparation of multi-layered composite structures, enabling the final composite material to possess functions such as promoting cell adhesion, resisting infection, and promoting osteolysis. This process combination is highly innovative.

[0013] 4) The multilayer composite coating material of this invention simultaneously possesses high bonding strength, excellent cell adhesion promotion function, efficient anti-infection effect, and significant osteopromoting function. The high bonding strength originates from the synergy of glow discharge cleaning, sandblasting micro-nano processing, and electrochemical deposition, ensuring tight bonding between the coating and the substrate, as well as between the layers within the coating. The cell adhesion promotion function is achieved through adhesion sites and biological signals provided by polydopamine and tanshinone b; the anti-infection function is accomplished by antibacterial ions released from the copper-zinc alloy antibacterial layer; and the osteopromoting function is achieved by polydopamine, tanshinone b, and Fe... 3+ They jointly regulate the proliferation, differentiation, and mineralization processes of osteoblasts. The synergistic effect of these functions enables this material to effectively address the complex needs of cell adhesion, infection control, and bone repair after bone implantation, providing an innovative solution for the surface function of implants in orthopedics and dentistry.

[0014] 5) The final mass ratio of the copper-zinc coating in this invention is controlled at copper:zinc = 75:25-30:70. This result stems from a precise and novel electrolyte formulation design, taking into account the coating performance balance issues encountered during actual coating development. Extensive experiments and EDS testing revealed that different ratios of copper and zinc ions in the electrolyte lead to varying coating uniformity. If the ratio is lower than the aforementioned mass ratio (i.e., the zinc proportion increases), the copper-zinc alloy will be unevenly dispersed, resulting in black, speckled coatings and a significant reduction in coating bonding strength. Conversely, if the ratio is higher than the aforementioned mass ratio (i.e., the copper proportion increases), the coating's biocompatibility will decrease, and excessive biotoxicity will render it unsuitable for applications in orthopedics, dentistry, and other fields. This invention, based on the actual application requirements of the materials, achieves final technological optimization and formulation innovation through continuous formulation adjustments and extensive testing results.

[0015] 6) In this invention, after the copper-zinc alloy coating is deposited, to further enhance the coating's ability to promote cell adhesion and bone integration, a sandblasting process is innovatively combined to introduce micro-nano topological structures onto the alloy coating surface. Although the technology of introducing topological structures by sandblasting on metal surfaces is relatively mature in the corresponding field, this invention further sandblasts the already deposited metal coating substrate to form micro-nano structures, which is a modification of the coating rather than a traditional modification of the substrate. This approach is significantly innovative, and the process achieves a completely new application. Furthermore, introducing micro-nano structures into the metal coating substrate in the aforementioned sandblasting process presents technical difficulties. For example, the sandblasting power and sandblasting time will affect the integrity of the coating and the bonding strength between the coating and the substrate, and the particle size of the sand particles will affect the pore size and actual morphological differences of the micro-nano structures. This invention, however, combines the results of cell experiments, animal experiments, and physicochemical property testing to optimize the process parameters, rather than simply transferring the sandblasting process to the construction of micro-nano topological structures on the metal coating surface. The technology has significant application innovation.

[0016] 7) The technology in this invention has obvious convenience and universality. It can be used to modify the surface of titanium-based orthopedic and dental instruments. The resulting composite coating can achieve efficient anti-infection and bone-promoting effects, and can realize functional innovation of traditional dental and orthopedic instruments. Attached Figure Description

[0017] Figure 1 A schematic diagram of the preparation process of an organic-inorganic multilayer composite coating material that combines cell adhesion promotion, anti-infection, and osteoproliferative functions; Figure 2 SEM image of an organic-inorganic multilayer composite coating material with functions of promoting cell adhesion, anti-infection and promoting osteolysis after sandblasting on a copper-zinc coated surface. Figure 3The results of CCK-8 co-culture of BMSCs with extracts of organic-inorganic multilayer composite coating materials that have the functions of promoting cell adhesion, anti-infection and promoting osteolysis. Figure 4 Organic-inorganic multilayer composite coating material with functions of promoting cell adhesion, anti-infection and promoting osteolysis was used in a rabbit intramedullary infection model. The results of the tissue fluid coating around the sample were obtained (A is Example 1, B is Example 4). Figure 5 X-ray results of a rabbit intramedullary infection model using an organic-inorganic multilayer composite coating material that combines cell adhesion promotion, anti-infection, and osteoproliferative functions (A is Example 1, B is Example 4). Detailed Implementation

[0018] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific examples.

[0019] Example 1: 1) The TC4 titanium alloy sample was treated using a suction-type pneumatic sandblasting system: The system was driven by a 250W motor and a 7.5kW air compressor, with the working air pressure set at 0.55MPa. 100-mesh and 210-mesh white corundum abrasive particles were used sequentially. The abrasive particles were accelerated by compressed air and sprayed onto the sample surface at a speed of approximately 75m / s. During the sandblasting process, the spray gun maintained a 45° spray angle and a 200mm spray distance from the sample surface, with a sandblasting time of 15s. After the above treatment, a rough surface with a micro-nano composite structure was formed on the surface of the titanium alloy sample, with a surface roughness (Ra) of approximately 1.2 micrometers. The sample was then placed in an ultrasonic cleaning solution containing 25 g / L sodium hydroxide, 12 g / L sodium carbonate, 12 g / L sodium metasilicate pentahydrate, 4 g / L fatty alcohol polyoxyethylene ether, 3 g / L sodium citrate, 2 g / L sodium polyacrylate, and 0.8 g / L benzotriazole, with the remainder being deionized water. The sample was ultrasonically cleaned for 25 minutes at a constant temperature of 55°C and an ultrasonic degreasing power of 150 W. It was then rinsed three times with deionized water for 10 minutes each time. Subsequently, the surface moisture was dried by blowing with high-purity nitrogen at a flow rate of 10 m / s, and then dried in a forced-air dryer at 60°C for 30 minutes. Finally, the sample was placed in a vacuum chamber and evacuated to a vacuum level of 5 × 10⁻⁶. -3After Pa, a mixed gas of argon at a flow rate of 50 sccm and oxygen at a flow rate of 120 sccm was injected, and the vacuum was evacuated again to 3 Pa. The workpiece was then subjected to a 600V negative bias and a 60% duty cycle for 900 seconds at 168℃ to complete the glow discharge cleaning. After cooling to room temperature, the sample was placed in an electrolyte solution composed of 35 g / L copper pyrophosphate, 15 g / L zinc sulfate, 200 g / L potassium pyrophosphate, 10 g / L sodium citrate, 14 g / L sodium sulfate, 6 g / L sodium hydroxide, 1.5 g / L polyethylene glycol 4000, 0.5 g / L potassium antimony tartrate, and deionized water, with a pH of 10. Copper was used as the anode and the sample as the cathode. The electrolyte temperature was controlled at 50℃, and the pressure was maintained at 0.5 A / dm³. 2 A copper-zinc alloy coating of approximately 10 micrometers was deposited for 50 minutes under conditions of dual-pulse power supply (50% duty cycle), mechanical stirring at 80 rpm / min, and continuous electrolyte filtration. The coating was then washed three times with deionized water for 15 minutes each time, dried with nitrogen, and baked at a low temperature for 20 minutes. After cooling to room temperature, it was ready for the next step. The mass ratio of copper to zinc in the obtained copper-zinc coating was approximately 75:25.

[0020] 2) The above sample was subjected to a suction-type pneumatic sandblasting system. Under the action of 0.7MPa compressed air pressure provided by a 350W drive motor and a 9kW air compressor, 220 mesh green silicon carbide was sprayed at a speed of 50m / s through a spray gun at a 60° shooting angle and a dynamic spray angle distance of 100mm for 30s. A microporous structure with a pore size of about 1 micrometer was controllably constructed on its surface. Subsequently, it was cleaned with deionized water 3 times, 15min each time.

[0021] 3) The above sample was placed in a dopamine PDA coating solution containing 8 g / L dopamine hydrochloride, 3.5 g / L chitosan, 2.5 g / L polyvinylpyrrolidone, 60 mg / L nano hydroxyapatite, and Tris-HCl buffer solution with pH 8.5 as solvent. The polymerization reaction was carried out at 30°C for 15 h. After that, the polymerized sample was immersed in ferric chloride aqueous solution with a concentration of 0.05 mol / L at 28°C for 50 min to complete the chelation. The sample surface was rinsed three times with deionized water.

[0022] 4) The above sample was immersed in a chelation solution prepared with 2 g / L tanshinone b, 100 mL / L ethanol, 0.5 g / L ascorbic acid, 8 g / L sodium chloride, 0.075 g / L sodium hyaluronate, 0.8 g / L chitosan quaternary ammonium salt, and 10 mM Tris-HCl buffer (pH 7.4) as the solvent system. The sample was ultrasonically treated at 35°C with 40 W power for 20 minutes, followed by rinsing with deionized water three times for 15 minutes each time, and then drying the surface with high-purity nitrogen gas at 15 m / s. This process was repeated six times. The sample was then dried in a forced-air drying system at 50°C for 50 minutes, vacuum-sealed in an aluminum foil bag to protect it from light, and finally subjected to 25 kGy... 60 The organic-inorganic multilayer composite coating material, which combines cell adhesion promotion, anti-infection, and osteopromoting functions, was prepared by Co irradiation sterilization.

[0023] 5) The bonding strength of the above coating material was 32.6 MPa, which decreased to 27.1 MPa after secondary sandblasting. An extract of the above material was prepared and subjected to a 24-hour CCK-8 assay with bone marrow mesenchymal stem cells (BMSCs). The results showed that the cell viability was 92.6% compared to the blank control group (i.e., cultured only in culture medium without additional extract). Co-culturing BMSCs on the surface of the above samples resulted in greater cell adhesion and better cell spreading compared to ordinary TC4 samples. An inhibition zone experiment was performed on a 1cm*1cm sample, and the inhibition zone area was 2.82 cm². 2 The above samples were combined with a rabbit intramedullary infection model to verify the effect. After 2 weeks, the gross examination showed that there was basically no infection. The tissue fluid smear around the sample showed that there was basically no colony formation. Furthermore, the Micro-CT results after 4 weeks showed that there was obvious new bone formation on the sample surface.

[0024] Example 2: 1) The TC4 titanium alloy sample was treated using a suction-type pneumatic sandblasting system: The system was driven by a 250W motor and a 7.5kW air compressor, with the working air pressure set at 0.55MPa. 100-mesh and 210-mesh white corundum abrasive particles were used sequentially. The abrasive particles were accelerated by compressed air and sprayed onto the sample surface at a speed of approximately 75m / s. During the sandblasting process, the spray gun maintained a 45° spray angle and a 200mm spray distance from the sample surface, with a sandblasting time of 15s. After the above treatment, a rough surface with a micro-nano composite structure was formed on the surface of the titanium alloy sample, with a surface roughness (Ra) of approximately 1.2 micrometers. The sample was then placed in an ultrasonic cleaning solution containing 25 g / L sodium hydroxide, 12 g / L sodium carbonate, 12 g / L sodium metasilicate pentahydrate, 4 g / L fatty alcohol polyoxyethylene ether, 3 g / L sodium citrate, 2 g / L sodium polyacrylate, and 0.8 g / L benzotriazole, with the remainder being deionized water. The sample was ultrasonically cleaned for 25 minutes at a constant temperature of 55°C and an ultrasonic power of 150 W. It was then rinsed three times with deionized water for 10 minutes each time. Subsequently, the surface moisture was dried by blowing with high-purity nitrogen at a flow rate of 10 m / s, followed by drying at 60°C with forced air for 30 minutes. Finally, the sample was placed in a vacuum chamber and evacuated to a vacuum level of 5 × 10⁻⁶. -3 After Pa, a mixed gas of argon at a flow rate of 50 sccm and oxygen at a flow rate of 120 sccm was injected, and the vacuum was evacuated again to 3 Pa. The workpiece was then subjected to a 600V negative bias and a 60% duty cycle for 900 seconds at 168℃ to complete the glow discharge cleaning. After cooling to room temperature, the sample was placed in an electrolyte solution composed of 35 g / L copper pyrophosphate, 15 g / L zinc sulfate, 200 g / L potassium pyrophosphate, 10 g / L sodium citrate, 14 g / L sodium sulfate, 6 g / L sodium hydroxide, 1.5 g / L polyethylene glycol 4000, 0.5 g / L potassium antimony tartrate, and deionized water, with a pH of 10. Copper was used as the anode and the sample as the cathode. The electrolyte temperature was controlled at 50℃, and the pressure was maintained at 0.5 A / dm³. 2 A copper-zinc alloy coating of approximately 10 micrometers was deposited under conditions of dual-pulse power supply (50% duty cycle), mechanical stirring at 80 rpm / min, and continuous electrolyte filtration for 50 min. The coating was then washed three times with deionized water for 15 min each time, dried with nitrogen, and baked at a low temperature for 20 min. After cooling to room temperature, it awaited the next step. The mass ratio of copper to zinc in the obtained copper-zinc coating was approximately 75:25.

[0025] 2) The above sample was subjected to a suction-type pneumatic sandblasting system. Under the action of 0.7MPa compressed air pressure provided by a 350W drive motor and a 9kW air compressor, 220 mesh green silicon carbide was sprayed at a speed of 50m / s through a spray gun at a 60° shooting angle and a dynamic spray angle distance of 100mm for 30s. A microporous structure with a pore size of about 1 micrometer was controllably constructed on its surface. Subsequently, it was cleaned with deionized water 3 times, 15min each time.

[0026] 3) The above sample was placed in a dopamine PDA coating solution containing 8 g / L dopamine hydrochloride, 3.5 g / L chitosan, 2.5 g / L polyvinylpyrrolidone, 60 mg / L nano-hydroxyapatite, and a Tris-HCl buffer solution at pH 8.5 as the solvent. Polymerization was carried out at 30°C for 15 h. Afterward, the polymerized sample was immersed in a 0.05 mol / L ferric chloride aqueous solution at 28°C for 50 min to complete chelation. The sample surface was rinsed three times with deionized water for 15 min each time, and then dried with high-purity nitrogen gas at 15 m / s. This process was repeated six times. Finally, the sample was dried in a forced-air drying oven at 50°C for 50 min, vacuum-sealed in an aluminum foil bag to protect it from light, and then subjected to a 25 kGy test. 60 The desired coating material is obtained after sterilization by Co irradiation.

[0027] 5) Compared to Example 1, this example reduces the introduction of tanshinone b. The bonding strength of the copper-zinc coating was 32.8 MPa, which decreased to 26.8 MPa after secondary sandblasting. The extract of the above material was prepared and subjected to a 24-hour CCK-8 assay with BMSCs. The results showed that the cell viability was 89.4% compared to the blank control group. Co-culturing BMSCs on the surface of the above samples showed a significant reduction in cell adhesion compared to the example, and the cell spreading was also inferior to that in Example 1. An inhibition zone experiment was performed on a 1cm*1cm sample, and the inhibition zone area was 3.16 cm². 2 The above samples were combined with a rabbit intramedullary infection model to verify the effect. After 2 weeks, the gross examination showed that there was basically no infection. The tissue fluid smear around the sample showed that there was basically no colony formation. The Micro-CT results after 4 weeks showed that there was obvious new bone formation on the sample surface, but the effect of new bone formation was slightly lower than that in Example 1.

[0028] Example 3: 1) The TC4 titanium alloy sample was treated using a suction-type pneumatic sandblasting system: The system was driven by a 250W motor and a 7.5kW air compressor, with the working air pressure set at 0.55MPa. 100-mesh and 210-mesh white corundum abrasive particles were used sequentially. The abrasive particles were accelerated by compressed air and sprayed onto the sample surface at a speed of approximately 75m / s. During the sandblasting process, the spray gun maintained a 45° spray angle and a 200mm spray distance from the sample surface, with a sandblasting time of 15s. After the above treatment, a rough surface with a micro-nano composite structure was formed on the surface of the titanium alloy sample, with a surface roughness (Ra) of approximately 1.2 micrometers. The sample was then placed in an ultrasonic cleaning solution containing 25 g / L sodium hydroxide, 12 g / L sodium carbonate, 12 g / L sodium metasilicate pentahydrate, 4 g / L fatty alcohol polyoxyethylene ether, 3 g / L sodium citrate, 2 g / L sodium polyacrylate, and 0.8 g / L benzotriazole, with the remainder being deionized water. The sample was ultrasonically cleaned for 25 minutes at a constant temperature of 55°C and an ultrasonic power of 150 W. It was then rinsed three times with deionized water for 10 minutes each time. Subsequently, the surface moisture was dried by blowing with high-purity nitrogen at a flow rate of 10 m / s, followed by drying at 60°C with forced air for 30 minutes. Finally, the sample was placed in a vacuum chamber and evacuated to a vacuum level of 5 × 10⁻⁶. -3 After Pa, a mixed gas of argon at a flow rate of 50 sccm and oxygen at a flow rate of 120 sccm was injected, and the vacuum was evacuated again to 3 Pa. The workpiece was then subjected to a 600V negative bias and a 60% duty cycle for 900 seconds at 168℃ to complete the glow discharge cleaning. After cooling to room temperature, the sample was placed in an electrolyte solution composed of 35 g / L copper pyrophosphate, 15 g / L zinc sulfate, 200 g / L potassium pyrophosphate, 10 g / L sodium citrate, 14 g / L sodium sulfate, 6 g / L sodium hydroxide, 1.5 g / L polyethylene glycol 4000, 0.5 g / L potassium antimony tartrate, and deionized water, with a pH of 10. Copper was used as the anode and the sample as the cathode. The electrolyte temperature was controlled at 50℃, and the pressure was maintained at 0.5 A / dm³. 2 A copper-zinc alloy coating of approximately 10 micrometers was deposited under conditions of dual-pulse power supply (50% duty cycle), mechanical stirring at 80 rpm / min, and continuous electrolyte filtration for 50 min. The coating was then washed three times with deionized water for 15 min each time, dried with nitrogen, and baked at a low temperature for 20 min. After cooling to room temperature, it awaited the next step. The mass ratio of copper to zinc in the obtained copper-zinc coating was approximately 75:25.

[0029] 2) The above sample was placed in a dopamine PDA coating solution containing 8 g / L dopamine hydrochloride, 3.5 g / L chitosan, 2.5 g / L polyvinylpyrrolidone, 60 mg / L nano hydroxyapatite, and Tris-HCl buffer solution with pH 8.5 as solvent. The polymerization reaction was carried out at 30°C for 15 h. After that, the polymerized sample was immersed in ferric chloride aqueous solution with a concentration of 0.05 mol / L at 28°C for 50 min to complete the chelation. The sample surface was rinsed three times with deionized water.

[0030] 3) The above sample was immersed in a chelation solution prepared with 2 g / L tanshinone b, 100 mL / L ethanol, 0.5 g / L ascorbic acid, 8 g / L sodium chloride, 0.075 g / L sodium hyaluronate, 0.8 g / L chitosan quaternary ammonium salt, and 10 mM Tris-HCl buffer (pH 7.4) as the solvent system. The sample was ultrasonically treated at 35°C with 40 W power for 20 minutes, followed by rinsing with deionized water three times for 15 minutes each time, and drying the surface with high-purity nitrogen gas at 15 m / s. This process was repeated six times. The sample was then dried in a forced-air drying system at 50°C for 50 minutes, vacuum-sealed in an aluminum foil bag to protect it from light, and finally subjected to 25 kGy... 60 The desired coating material is obtained after sterilization by Co irradiation.

[0031] 4) Compared to Example 1, this example reduces the introduction of micro-nanoporous structures on the copper-zinc coating surface. The bonding strength of the copper-zinc coating is 31.9 MPa. The extract of the above material was subjected to a 24-hour CCK-8 assay with BMSCs, and the results showed that the cell viability was 90.6% compared to the blank control group. Co-culturing BMSCs on the sample surface showed a decrease in cell adhesion and spread compared to Example 1, with both cell adhesion and spread being inferior to Example 2. An inhibition zone experiment was performed on a 1cm*1cm sample, and the inhibition zone area was 2.54 cm². 2 The above samples were combined with a rabbit intramedullary infection model to verify the effect. After 2 weeks, the gross examination showed that there was basically no infection. The tissue fluid smear around the sample showed that there was basically no colony formation. The Micro-CT results after 4 weeks showed that there was obvious new bone formation on the sample surface, but the amount of new bone formation was slightly less than that in Examples 1 and 2.

[0032] Example 4: 1) The TC4 titanium alloy sample was treated using a suction-type pneumatic sandblasting system: The system was driven by a 250W motor and a 7.5kW air compressor, with the working air pressure set at 0.55MPa. 100-mesh and 210-mesh white corundum abrasive particles were used sequentially. The abrasive particles were accelerated by compressed air and sprayed onto the sample surface at a speed of approximately 75m / s. During the sandblasting process, the spray gun maintained a 45° spray angle and a 200mm spray distance from the sample surface, with a sandblasting time of 15s. After the above treatment, a rough surface with a micro-nano composite structure was formed on the surface of the titanium alloy sample, with a surface roughness (Ra) of approximately 1.2 micrometers. The sample was then placed in an ultrasonic cleaning solution containing 25 g / L sodium hydroxide, 12 g / L sodium carbonate, 12 g / L sodium metasilicate pentahydrate, 4 g / L fatty alcohol polyoxyethylene ether, 3 g / L sodium citrate, 2 g / L sodium polyacrylate, and 0.8 g / L benzotriazole, with the remainder being deionized water. The sample was ultrasonically cleaned for 25 minutes at a constant temperature of 55°C and an ultrasonic power of 150 W. It was then rinsed three times with deionized water for 10 minutes each time. Subsequently, the surface moisture was dried by blowing with high-purity nitrogen at a flow rate of 10 m / s, followed by drying at 60°C with forced air for 30 minutes. Finally, the sample was placed in a vacuum chamber and evacuated to a vacuum level of 5 × 10⁻⁶. -3 After Pa, a mixed gas of argon at a flow rate of 50 sccm and oxygen at a flow rate of 120 sccm was injected, and the vacuum was evacuated again to 3 Pa. The workpiece was then subjected to a 600V negative bias and a 60% duty cycle for 900 seconds at 168℃ to complete the glow discharge cleaning. After cooling to room temperature, the sample was placed in an electrolyte solution with a pH of 10, consisting of 45 g / L zinc sulfate, 200 g / L potassium pyrophosphate, 10 g / L sodium citrate, 14 g / L sodium sulfate, 6 g / L sodium hydroxide, 1.5 g / L polyethylene glycol 4000, 0.5 g / L potassium antimony tartrate, and deionized water. Copper was used as the anode and the sample as the cathode. The electrolyte temperature was controlled at 50℃, and the pressure was maintained at 0.5 A / dm³. 2 Deposition was carried out for 50 minutes under the conditions of dual-pulse power supply (duty cycle 50%), mechanical stirring at 80 rpm / min and continuous filtration of electrolyte to obtain a zinc elemental coating of about 10 micrometers. Then, it was washed three times with deionized water for 15 minutes each time, dried with nitrogen, and baked at low temperature for 20 minutes. After cooling to room temperature, it was ready for the next step.

[0033] 2) The above sample was subjected to a suction-type pneumatic sandblasting system. Under the action of 0.7MPa compressed air pressure provided by a 350W drive motor and a 9kW air compressor, 220 mesh green silicon carbide was sprayed at a speed of 50m / s through a spray gun at a 60° shooting angle and a dynamic spray angle distance of 100mm for 30s. A microporous structure with a pore size of about 1 micrometer was controllably constructed on its surface. Subsequently, it was cleaned with deionized water 3 times, 15min each time.

[0034] 3) The above sample was placed in a dopamine PDA coating solution containing 8 g / L dopamine hydrochloride, 3.5 g / L chitosan, 2.5 g / L polyvinylpyrrolidone, 60 mg / L nano hydroxyapatite, and Tris-HCl buffer solution with pH 8.5 as solvent. The polymerization reaction was carried out at 30°C for 15 h. After that, the polymerized sample was immersed in ferric chloride aqueous solution with a concentration of 0.05 mol / L at 28°C for 50 min to complete the chelation. The sample surface was rinsed three times with deionized water.

[0035] 4) The above sample was immersed in a chelation solution prepared with 2 g / L tanshinone b, 100 mL / L ethanol, 0.5 g / L ascorbic acid, 8 g / L sodium chloride, 0.075 g / L sodium hyaluronate, 0.8 g / L chitosan quaternary ammonium salt, and 10 mM Tris-HCl buffer (pH 7.4) as the solvent system. The sample was ultrasonically treated at 35°C with 40 W power for 20 minutes, followed by rinsing with deionized water three times for 15 minutes each time, and then drying the surface with high-purity nitrogen gas at 15 m / s. This process was repeated six times. The sample was then dried in a forced-air drying system at 50°C for 50 minutes, vacuum-sealed in an aluminum foil bag to protect it from light, and finally subjected to 25 kGy... 60 The desired coating material is obtained after sterilization by Co irradiation.

[0036] 5) Compared to Example 1, this example reduces electrochemical deposition on copper to obtain a pure zinc coating. The bonding strength of the zinc coating was 22.7 MPa, which decreased to 17.9 MPa after secondary sandblasting. The extract of the above material was prepared and subjected to a 24-hour CCK-8 assay with BMSCs. The results showed that the cell viability was 81.4% compared to the blank control group. Co-culturing BMSCs on the sample surface significantly reduced cell adhesion and spreading compared to Example 1. An inhibition zone experiment was performed on a 1cm*1cm sample, with virtually no inhibition zone formation. The above samples were used to verify the effectiveness in a rabbit intramedullary infection model. Infection was confirmed after 2 weeks, with redness, swelling, and purulent discharge. A smear of tissue fluid around the sample showed a large number of colonies. Micro-CT scans at 4 weeks showed significant osteolysis in the rabbits, and X-ray results indicated significant osteomyelitis.

[0037] Example 5: 1) The TC4 titanium alloy sample was treated using a suction-type pneumatic sandblasting system: The system was driven by a 250W motor and a 7.5kW air compressor, with the working air pressure set at 0.55MPa. 100-mesh and 210-mesh white corundum abrasive particles were used sequentially. The abrasive particles were accelerated by compressed air and sprayed onto the sample surface at a speed of approximately 75m / s. During the sandblasting process, the spray gun maintained a 45° spray angle and a 200mm spray distance from the sample surface, with a sandblasting time of 15s. After the above treatment, a rough surface with a micro-nano composite structure was formed on the surface of the titanium alloy sample, with a surface roughness (Ra) of approximately 1.2 micrometers. The sample was then placed in an ultrasonic cleaning solution containing 25 g / L sodium hydroxide, 12 g / L sodium carbonate, 12 g / L sodium metasilicate pentahydrate, 4 g / L fatty alcohol polyoxyethylene ether, 3 g / L sodium citrate, 2 g / L sodium polyacrylate, and 0.8 g / L benzotriazole, with the remainder being deionized water. The sample was ultrasonically cleaned for 25 minutes at a constant temperature of 55°C and an ultrasonic power of 150 W. It was then rinsed three times with deionized water for 10 minutes each time. Subsequently, the surface moisture was dried by blowing with high-purity nitrogen at a flow rate of 10 m / s, followed by drying at 60°C with forced air for 30 minutes. Finally, the sample was placed in a vacuum chamber and evacuated to a vacuum level of 5 × 10⁻⁶. -3 After Pa, a mixed gas of argon at a flow rate of 50 sccm and oxygen at a flow rate of 120 sccm was injected, and the vacuum was evacuated again to 3 Pa. The workpiece was then subjected to a 600V negative bias and a 60% duty cycle for 900 seconds at 168℃ to complete the glow discharge cleaning. After cooling to room temperature, the sample was placed in an electrolyte solution composed of 35 g / L copper pyrophosphate, 15 g / L zinc sulfate, 200 g / L potassium pyrophosphate, 10 g / L sodium citrate, 14 g / L sodium sulfate, 6 g / L sodium hydroxide, 1.5 g / L polyethylene glycol 4000, 0.5 g / L potassium antimony tartrate, and deionized water, with a pH of 10. Copper was used as the anode and the sample as the cathode. The electrolyte temperature was controlled at 50℃, and the pressure was maintained at 0.5 A / dm³. 2 A copper-zinc alloy coating of approximately 10 micrometers was deposited under conditions of dual-pulse power supply (50% duty cycle), mechanical stirring at 80 rpm / min, and continuous electrolyte filtration for 50 min. The coating was then washed three times with deionized water for 15 min each time, dried with nitrogen, and baked at a low temperature for 20 min. After cooling to room temperature, it awaited the next step. The mass ratio of copper to zinc in the obtained copper-zinc coating was approximately 75:25.

[0038] 2) The above sample was subjected to a suction-type pneumatic sandblasting system. Under the action of 0.7MPa compressed air pressure provided by a 350W drive motor and a 9kW air compressor, 40-mesh green silicon carbide was sprayed at a speed of 50m / s through a spray gun at a 60° shooting angle and a dynamic spray angle distance of 100mm for 30s. A microporous structure with a pore size of about 50 micrometers was controllably constructed on its surface. Subsequently, it was cleaned with deionized water 3 times, 15min each time.

[0039] 3) The above sample was placed in a dopamine PDA coating solution containing 8 g / L dopamine hydrochloride, 3.5 g / L chitosan, 2.5 g / L polyvinylpyrrolidone, 60 mg / L nano hydroxyapatite, and Tris-HCl buffer solution with pH 8.5 as solvent. The polymerization reaction was carried out at 30°C for 15 h. After that, the polymerized sample was immersed in ferric chloride aqueous solution with a concentration of 0.05 mol / L at 28°C for 50 min to complete the chelation. The sample surface was rinsed three times with deionized water.

[0040] 4) The above sample was immersed in a chelation solution prepared with 2 g / L tanshinone b, 100 mL / L ethanol, 0.5 g / L ascorbic acid, 8 g / L sodium chloride, 0.075 g / L sodium hyaluronate, 0.8 g / L chitosan quaternary ammonium salt, and 10 mM Tris-HCl buffer (pH 7.4) as the solvent system. The sample was ultrasonically treated at 35°C with 40 W power for 20 minutes, followed by rinsing with deionized water three times for 15 minutes each time, and then drying the surface with high-purity nitrogen gas at 15 m / s. This process was repeated six times. The sample was then dried in a forced-air drying system at 50°C for 50 minutes, vacuum-sealed in an aluminum foil bag to protect it from light, and finally subjected to 25 kGy... 60 The desired coating material is obtained after sterilization by Co irradiation.

[0041] 5) Compared to Example 1, this example increases the pore size of the microporous structure on the copper-zinc surface. The bonding strength of the copper-zinc coating was 33.4 MPa, which decreased to 25.1 MPa after secondary sandblasting. An extract of the above material was prepared and subjected to a 24-hour CCK-8 assay with BMSCs. The results showed that the cell viability was 89.8% compared to the blank control group. Co-culturing BMSCs on the sample surface showed similar cell adhesion compared to Example 1, but better cell spreading. An inhibition zone experiment was performed on a 1cm*1cm sample, and the inhibition zone area was 3.17 cm². 2 The above samples were combined with a rabbit intramedullary infection model to verify the effect. After 2 weeks, the gross examination showed that there was basically no infection. The tissue fluid smear around the sample showed that there was basically no colony formation. Furthermore, the Micro-CT results after 4 weeks showed that there was obvious new bone formation on the sample surface, and the amount of new bone was slightly higher than that in Example 1.

Claims

1. A method for preparing an organic-inorganic multi-layer composite coating material with cell adhesion-promoting-anti-infection-bone formation-promoting functions, characterized in that: The preparation method comprises the following steps: 1) a first sand blasting treatment is performed on the titanium / titanium alloy sample, and then the surface oxide layer of the titanium / titanium alloy sample is removed by using an ultrasonic oil removal and glow discharge cleaning process in sequence, and an antibacterial and osteogenic copper / zinc alloy coating is constructed on the sample surface by an electrochemical deposition process; 2) a second sand blasting process is used to perform micro-nano processing on the coating to introduce a topological morphology conducive to cell adhesion. 3) deposition of polydopamine PDA coating on the surface using an in situ self- polymerization process, followed by immersion to complete Fe 3+ chelation with PDA; 4) Further use of the ultrasonic immersion process to achieve PDA-Fe 3+ chelation to PDA-Fe 3+ - transformation of the Danshensuan b chelation to introduce a Danshensuan b layer that promotes cell adhesion, after rinsing, air-drying and sterilization, the organic-inorganic multi-layer composite coating material with the functions of promoting cell adhesion-anti-infection-promoting osteogenesis is obtained.

2. The method for preparing the organic-inorganic multi-layer composite coating material with cell adhesion-promoting, anti-infective, and bone formation-promoting functions according to claim 1, characterized in that: In step 1), the first sand blasting process is as follows: the titanium / titanium alloy sample is treated by using a suction type pneumatic sand blasting system, 80-120 mesh and 200-220 mesh white corundum sand particles are accelerated to 50-100 m / s and sprayed onto the sample surface under a compressed air pressure of 0.4-0.7 MPa, the spray gun is aimed at the workpiece at an angle of 30-60° during the operation, a dynamic spray angle distance of 100-300 mm is maintained, and the sand blasting time is 5-30 s, and a micro-nano composite structure is formed on the sample surface.

3. The method for preparing organic-inorganic multi-layer composite coating material with cell adhesion-promoting, anti-infective, and bone formation-promoting functions according to claim 1, characterized in that: In step 1), the ultrasonic oil removal process is as follows: the sample is placed in an ultrasonic cleaning solution, the ultrasonic power is 100-180 W, the solution temperature is 50-60°C, and the sample is soaked for 20-30 min; then the sample is cleaned with deionized water; and the ultrasonic cleaning solution formula is as follows: sodium hydroxide 20-30 g / L, sodium carbonate 8-16 g / L, sodium metasilicate pentahydrate 10-15 g / L, fatty alcohol polyoxyethylene ether 3-5 g / L, sodium citrate 2-5 g / L, sodium polyacrylate 1-4 g / L, benzene propyl triazole 0.5-1 g / L, and the rest is deionized water.

4. The method for preparing organic-inorganic multi-layer composite coating material with cell adhesion-promoting, anti-infective, and bone formation-promoting functions according to claim 1, characterized in that: The glow discharge cleaning process in step 1) is as follows: the sample is placed in a vacuum chamber, vacuumed to 5*10 -3 After the pressure is reduced to 1-3 Pa, the sample is bombarded under the conditions of a temperature of 150-200℃, a negative bias of 600-1000V, a duty cycle of 50-80%, and a bombardment cleaning time of 900-1500s.

5. The method for preparing organic-inorganic multi-layer composite coating material with cell adhesion-promoting, anti-infective, and bone formation-promoting functions according to claim 1, characterized in that: The electrochemical deposition process in step 1) is as follows: the sample is placed in an electrolyte with pH of 9.5-11 and temperature of 45-50℃, copper is used as anode, the sample is used as cathode, a double pulse power source with duty cycle of 50% and mechanical stirring at 50-300rpm / min is used, and the electrolyte is continuously filtered, and the deposition is carried out for 30-130min to obtain a copper-zinc composite coating. 2 , duty cycle 50% and mechanical stirring at 50-300rpm / min is used, and the electrolyte is continuously filtered, and the deposition is carried out for 30-130min to obtain a copper-zinc composite coating. The electrolyte formula is as follows: copper pyrophosphate 25-35 g / L, zinc sulfate 15-50 g / L, potassium pyrophosphate 200-280 g / L, sodium citrate 10-18 g / L, potassium sulfate 12-25 g / L, sodium hydroxide 2-6 g / L, polyethylene glycol 40000 0.6-1.5 g / L, potassium antimony tartrate 0.5-0.9 g / L, and the rest is deionized water.

6. The method for preparing organic-inorganic multi-layer composite coating material with cell adhesion-promoting, anti-infective, and bone formation-promoting functions according to claim 5, characterized in that: The mass ratio of copper to zinc in the copper-zinc composite coating is controlled to be 75:25-30:

70.

7. The method for preparing organic-inorganic multi-layer composite coating material with cell adhesion-promoting, anti-infective, and bone formation-promoting functions according to claim 1, characterized in that: In step 2), the specific process of the second sand blasting is as follows: a suction type pneumatic sand blasting system is used, 20-300 mesh green silicon carbide abrasive is accelerated to 50-100 m / s and sprayed onto the coating surface under a compressed air pressure of 0.5-0.8 MPa, the spray gun is aimed at the workpiece at an angle of 30-60° during the operation, a dynamic spray angle distance of 100-300 mm is maintained, and the sand blasting time is 5-30 s, and a topological morphology containing 1-100 micrometer diameter pits is constructed on the surface.

8. The method for preparing the organic-inorganic multilayer composite coating material with cell adhesion promotion, anti-infection, and osteoproliferative functions according to claim 1, characterized in that: The in-situ self-polymerization process in step 3) is as follows: the sample is placed in a dopamine PDA coating solution, and polymerization is carried out at a temperature of 30-35℃ for 4-15h, and then the polymerized sample is immersed in a Fe 3+ aqueous solution for chelation; the dopamine PDA coating solution is a mixed solution of dopamine hydrochloride 2-8g / L, chitosan 2-5g / L, polyvinylpyrrolidone 2-4g / L, and nano-hydroxyapatite 20-100mg / L, with Tris-HCl buffer solution with a pH of 8.5-9 as the solvent; the Fe 3+ aqueous solution has a concentration of 0.02-0.10moL / L, and Fe 3+ comes from one or more of ferric chloride, ferric nitrate, and ferric sulfate, the solution temperature is 25-35℃, and the immersion time is 40-70min.

9. The method for preparing the organic-inorganic multilayer composite coating material with cell adhesion promotion, anti-infection, and osteoproliferative functions according to claim 1, characterized in that: The ultrasonic immersion process in step 4) is as follows: the sample is immersed in the Danshensuan chelating solution, ultrasonic treatment is carried out at 20-70 W power for 15-30 min at 25-35 °C, then the sample is washed with deionized water, the surface moisture is blown dry with high-purity nitrogen at a flow rate of 10-20 m / s, air-drying is carried out at 40-50 °C for 50 min, finally the sample is vacuum-packed in an aluminum foil bag in the dark, and the sample is stored at 2-8 °C. 60 The Co dose is 15-25 kGy for irradiation sterilization; the Danshensuan chelating solution is as follows: 10 mM Tris-HCl buffer (pH 7.4) is used as a solvent system, the Danshensuan chelating solution contains Danshensuan 2-3 g / L, ethanol 80-120 mL / L, ascorbic acid 0.5-1.2 g / L, sodium chloride 6-10 g / L, sodium hyaluronate 0.05-1 g / L, and chitosan quaternary ammonium salt 0.1-3 g / L.

10. Organic-inorganic multi-layer composite coating material having cell adhesion-promoting-anti-infection-bone formation-promoting functions, characterized by, The method is prepared by using any one of claims 1-9.

Citation Information

Patent Citations

  • Titanium alloy with antibacterial nano-porous copper zinc coating, preparation method and application

    CN111560635A